2(x+6)=4(3x)

Simple and best practice solution for 2(x+6)=4(3x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+6)=4(3x) equation:


Simplifying
2(x + 6) = 4(3x)

Reorder the terms:
2(6 + x) = 4(3x)
(6 * 2 + x * 2) = 4(3x)
(12 + 2x) = 4(3x)

Remove parenthesis around (3x)
12 + 2x = 4 * 3x

Multiply 4 * 3
12 + 2x = 12x

Solving
12 + 2x = 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
12 + 2x + -12x = 12x + -12x

Combine like terms: 2x + -12x = -10x
12 + -10x = 12x + -12x

Combine like terms: 12x + -12x = 0
12 + -10x = 0

Add '-12' to each side of the equation.
12 + -12 + -10x = 0 + -12

Combine like terms: 12 + -12 = 0
0 + -10x = 0 + -12
-10x = 0 + -12

Combine like terms: 0 + -12 = -12
-10x = -12

Divide each side by '-10'.
x = 1.2

Simplifying
x = 1.2

See similar equations:

| 4x-8=(x-4) | | 36+N=63 | | 3a+b-45=2a+4b+465.23+a+103b | | 13-x/7=-1 | | -1/5a+7=(-11) | | (x+2x+5)-10=22 | | 5/8x24 | | a/b-45=2a+4b+465.23+a+103b | | 1/4(8x-16)=6x+2 | | ab-45=2a+4b+465.23+a+103b | | -15-(-8)+7= | | ab-45=2a+4b+465.23+a+103ab | | -1-6k=-7k-19 | | 2+25p^2=66 | | 10a+15a=75 | | 2x+6=-6x-34 | | -7s+4=-7-8s+4 | | 6-7i/6+7i | | 60=-5x+10 | | 8v+35=7(6v+5) | | (1/2x)=32 | | 2g-14=g | | 4(y+2)=15 | | ab-45=2a+4b+465.23+a | | 156/180=x/120 | | (1-2x)=32 | | 13x-68=-7x+12 | | (1/3*9)3 | | 3x+26/5=7 | | n+3n=180 | | 0.8(m+4)-0.3m= | | 5x=-6x-22 |

Equations solver categories